PERTIMBANGAN HAKIM TERHADAP PERKARA CERAI GUGAT SUAMI GHAIB DAN AKIBAT HUKUMNYA DI PENGADILAN AGAMA KARAWANG - Baluqia, Singgih Hasanul; Priyana, Puti (Universitas Wiralodra, 2021)
Marriage is a sacred bond between a man and a woman as husband and wife. With the aim of creating a sakinah household, mawaddah wa rahmah. However, in reality there are many incompatibilities that happened between husband and wife in a journey of household, which in the end leads to not achieving the purpose of marriage which ends in divorce. There are many factors that trigger the occurrence of divorce, one of which is the disappearance of one party by leaving the other party without giving news for a long time and resulting in uncertainty about the status of the abandoned marriage. The purpose of this study is to find out and examine how judges consider divorce cases against unseen (ghaib) husbands and their legal consequences at the Karawang Religious Court. Research Methods in this scientific papers using normative juridical research methods. As well as using data collection techniques carried out using descriptive analysis techniques, with secondary data sources, which include primary legal materials such as laws and regulations relating to the rights of children and wives in divorce cases against unseen husbands, as well as secondary legal materials such as books. , journals, articles, and other legal doctrines. The results of the research that have been carried out basically in the judge's decision on the divorce case with the unseen husband which is the basis for the judge's consideration is the absence of the defendant whose his existence are unknown, namely the waiting period or iddah for the Plaintiff is set for at least 90 (ninety) days from the verdict has permanent legal force as intended by Article 11 paragraph (1) and paragraph (3) of Act Number 1 of 1974 jo. Article 39 Government Regulation Number 9 of 1975 paragraph (1) letter (b) jo. Article 153 paragraph (2) letter (b) and Article 153 paragraph (4) Compilation of Islamic Law (KHI), and the issuance of a certificate of occultation from the local village.